A Polyvinyl acetate emulsion plant - Bartolome, Francisco M.; Samson, Felix S.; Santiago, Jose S. Jr. (Quezon City College of Engineering, 1962)
This design project which enjoins all the many faculties that are part of the detailed passages from an initial idea to a complete industrial plant strongly contends that at the now existing economic and industrial atmosphere in the Philippines, the polyvinyl acetate emulsion plant offers a flourishing investment. The preliminary survey which consists of the examination of the technical and economic factors of the process of manufacturing the polyvinyl acetate emulsion, the consideration of the various reactions and the physical processes involved, along with the existing and potential market conditions for the particular product, gives and immediate indication of the probable success of the project. In conjunction with the indication that the project would be a commercial success, the known manufacturing processes were studied and the particular process suited to our economic environment chosen; material and energy balances made; process conditions examined for temperature and pressure variation, yield rates, grades of the product, operating characteristics and other pertinent design variables. All these permit the preparation of the flow sheet and the design and specification of equipment. A complete plant lay-out was prepared, with the piping diagrams and other construction details included. To finalize the pre-construction stage, cost estimation were made, fixed and operating expenses which constitute the initial capital investment determined, and the rates of return and the effects of varying production rate were investigated with the aid of the break even chart. The calculation and cost estimations call for the erection of the polyvinyl acetate emulsion plant: a. Operating at the maximum capacity of 7,488,000 pounds of polyvinyl acetate emulsion per annum and selling at low bulk price of P 0.70 per pound of the emulsion, the return on the total capital investment (before taxes) is 51.5%.
Typescript.
Plant design.
Keywords: Factories -- Design and construction; Vinyl acetate; Emulsions